1998
DOI: 10.3406/paleo.1998.4667
|View full text |Cite
|
Sign up to set email alerts
|

Hallan Çemi, pig husbandry, and post-Pleistocene adaptations along the Taurus-Zagros Arc (Turkey)

Abstract: Recent work at Hallan Çemi and other round house horizon sites in eastern Anatolia indicates that the Taurus-Zagros flanks were a second autochthonous center of neolithization in southwestern Asia. Fully settled complex hunter-gatherer societies are in existence in this area by the late Younger Dryas. These settled village societies were based on adaptations that did not involve cereal exploitation, presumably because cereals were absent in this area during the late Younger Dryas. Instead, these adaptations re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 1 publication
0
33
0
6
Order By: Relevance
“…This clearly demonstrates a long period of management in the wild (6) before morphological change attributable to domestication, as observed at Nevalı Ç ori (2). Such an intermediate wild-domestic status in both the Upper Tigris valley (3)(4)(5) and Cyprus indicates that pre-Neolithic wild boar management could have been practiced from Eastern Anatolia to the Mediterranean coast. Even if these suids were still wild, this practice appears to be an early step in the domestication process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This clearly demonstrates a long period of management in the wild (6) before morphological change attributable to domestication, as observed at Nevalı Ç ori (2). Such an intermediate wild-domestic status in both the Upper Tigris valley (3)(4)(5) and Cyprus indicates that pre-Neolithic wild boar management could have been practiced from Eastern Anatolia to the Mediterranean coast. Even if these suids were still wild, this practice appears to be an early step in the domestication process.…”
Section: Discussionmentioning
confidence: 99%
“…also implies that wild boar were already managed on the continent at that time (i.e., 1,500 years before the earliest attested domestication) (2). Management in the wild during the Younger Dryas has been suggested for gazelles [Natufian (32)], goats [Zarzian (33)], and wild boar [Late Natufian (4,5)]. Genetic analyses of the existing populations of the ancestor of the domestic goat, the bezoar goat (Capra aegagrus), have recently indicated that management of this goat occurred over a very large area, from Eastern Anatolia to the Iranian Central Zagros, and probably predated domestication (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faunal remains from Hallan Çemi are remarkably species diverse, comprised of both large and medium bodied game (caprines, red deer, and pig), as well as a wide array of small game animals in which hares, foxes, various bird species, and tortoises are particularly well represented. In a series of articles, Redding and Rosenberg have argued that residents of Hallan Çemi practiced an early form of pig management similar to modern pig husbandry practices in New Guinea, in which managed female pigs are allowed to breed with free-living males (Redding, 2005;Redding andRosenberg, 1998, 2000;Rosenberg et al, 1998). Dental eruption and wear data for the Hallan Çemi pigs was recorded using this system by Ximena Lemoine and Melinda Zeder as part of a larger study of this assemblage.…”
Section: Site Descriptionsmentioning
confidence: 99%
“…More species have been pushed into the 9000-11,000 BP time frame that Jim specified. Pig and cattle domestication have been pushed back in time as far back as sheep and goats (10,000-11,000 BP for pigs [Rosenberg et al 1998] and 10,000-10,800 BP for cattle, with North Africa emerging as an early center for their domestication; (Hanotte et al 2002)). Many animal species thus appear to have been domesticated virtually simultaneously throughout the Near East and North Africa.…”
Section: Resultsmentioning
confidence: 99%